IMPLEMENTING A NEW CURRICULUM WITH SPECIFIC REFERENCE TO HOME ECONOMICS IN PRIMARY SCHOOLS IN BINDURA DISTRICT IN ZIMBABWE - MUZENDA, DR. VERITY (IJRDO- Journal of Educational Research, 2017)
Home economics is a relatively new subject in Zimbabwe, having been introduced in the late 1990s. Before then, most schools offered subjects like Carpentry for boys and Domestic Science for girls. These subjects were taught by specialist teachers and as such, did not involve ordinary classroom practitioners. Home Economics seeks to develop in the youths an appreciation of their role in the solution of their own problems, and in the maintenance and upgrading of their living environment. Home Economics is aimed at promoting understanding of basic concepts of nutrition, hygiene, clothing, consumerism and family life. Pupils in the end learn to cook, do craftwork, launder their clothes, clean the home environment, improve sanitation levels in the school and community, plan their time and use it efficiently, budget their income, behave in acceptable ways, conserve resources and be good consumers. Important as Home Economics may appear to be particularly in the eyes of the policy makers, its introduction meant that teachers taking junior classes found themselves teaching as many as eleven different subjects in a single day. This may lead to an indifferent attitude among some teachers towards the new subject and hence that the subject does not receive the attention and importance it deserves. The introduction of Home Economics in the primary system in Zimbabwe represents a change. Its successful implementation will take time and move through a series of phases. It requires changing teachers’ attitudes and feelings. It also requires that teachers’ capacities be built in order to improve their mastery of the new content and teaching strategies. In the Zimbabwean context, the school principal / head is at the centre of the implementation of all new curricula at school level. In view of the above, this study sought to establish the support provided by school heads to teachers as they implement the Home Economics curriculum. The study employed the descriptive survey method. The study was conducted in Bindura District in Mashonaland Central Province in Zimbabwe. Random sampling was used to come up with a sample of 59 headmasters / mistresses from a total of 120 heads in the district, and 82 teachers from a total of 2 000 teachers in the district. Data were collected by means of semi-structured questionnaire. The main findings revealed that principals had no clear vision of the new curriculum. There is little effort put by principals towards the provision of resources, supervision of teachers is inadequate, there is no provision of technical assistance to teachers on the new curriculum. Heads, however, do make attempts to remove blockages which may inhibit the progress of implementation of the new curriculum. Based on the analysts of data, conclusions and recommendations were made.